2007
DOI: 10.1017/s1478061507736459
|View full text |Cite
|
Sign up to set email alerts
|

Practical assessment of heart rate response to exercise under field conditions

Abstract: Regular monitoring of the heart rate (HR):speed relationship may help evaluate response to training and aid in the early detection of problems. This relationship is normally determined using a treadmill or via a ridden test conducted outside on a track. Simple practical alternative methods to obtain this relationship without access to a treadmill or a track could be of value in the field. To evaluate whether the HR:speed relationship could be determined via an indoor ridden test or a lunge test, HR was monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 10 publications
5
25
0
Order By: Relevance
“…The data indicated that our methods used for training the Thoroughbreds under field conditions were satisfactory for maximization of physiological adaptations within the animal's body. HRs at rest ranged from 32 to 37 beats/min and were similar to the values obtained by Harris et al [18]. Peak HRs during cantering/galloping were approximately 200 beats/min and remained the same during both the training and the racing seasons.…”
Section: Supplements Versus Placebo At Rest and After Exercisesupporting
confidence: 87%
“…The data indicated that our methods used for training the Thoroughbreds under field conditions were satisfactory for maximization of physiological adaptations within the animal's body. HRs at rest ranged from 32 to 37 beats/min and were similar to the values obtained by Harris et al [18]. Peak HRs during cantering/galloping were approximately 200 beats/min and remained the same during both the training and the racing seasons.…”
Section: Supplements Versus Placebo At Rest and After Exercisesupporting
confidence: 87%
“…Effects of excitability cannot be ruled out; expectation may explain the higher basal HR for TRT 4 and 5. Excitability can notably affect results when HR values are below 160 bpm (Harris et al, 2007). Horses 1 and 5 had significantly different HR (P<0.05) (data not shown).…”
Section: Resultsmentioning
confidence: 94%
“…Basal HR was significantly higher during TRT 4 and 5, (table 1). Different ground surfaces, (Sloet van Oldruitenborgh-Osterbaan and Barnevald, 1995), different energy needs for different activities (Lawrence, 1997), or environmental factors (Harris et al, 2007) are a few possible reasons for the differences in average and basal HR measured. Effects of excitability cannot be ruled out; expectation may explain the higher basal HR for TRT 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations